MATURATION AND SPAWNING IN POLYNEMUS HEPTADACTYLUS CUV. AND VAL. - Kagwade, P V (Indian Journal of Fisheries, 2011)
The maturity cycle of Pclynemus heptadactyius has been described. The ripe ovameasure 0.64 -1.04 mm in diameter, and each ovum contains one to many oil globules.Size at first maturity is 133 mm in female and 128 mm in males, when the fish has completedits second year of life. Females dominated in number in almost all length groups.Males were totally absent in length groups above 203 mm. Spawning is prolonged, andthe release of ova is in batches. Individual fish spawns twice with an interval of sixmonths; but with slight diversities in their individual spawning periods, the spawningof the species appears to be throughout the year. All the maturity stages are obtainedall through the year. There are two peak spawning seasons, March-June andAugust-November, and two recruitments every year. The spawning intensity seemsgreater in ofTshore waters. The fish appears to spend the juvenile stages in inshore waters